2017
DOI: 10.2807/1560-7917.es.2017.22.7.30463
|View full text |Cite
|
Sign up to set email alerts
|

Multinational outbreak of travel-related Salmonella Chester infections in Europe, summers 2014 and 2015

Abstract: Between 2014 and 2015, the European Centre for Disease Prevention and Control was informed of an increase in numbers of Salmonellaenterica serotype Chester cases with travel to Morocco occurring in six European countries. Epidemiological and microbiological investigations were conducted. In addition to gathering information on the characteristics of cases from the different countries in 2014, the epidemiological investigation comprised a matched case–case study involving French patients with salmonellosis who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…In addition, several studies have reported an increased UV resistance in environmental bacteria and bacterial spores, compared to laboratory-grown strains (Hijnen et al 2006). Previous studies have proven that some bacteria genus can easily cross the treatment process, while remaining are viable (Eddabra et al 2011;Fonteneau et al 2017); and this is further confirmed by the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, several studies have reported an increased UV resistance in environmental bacteria and bacterial spores, compared to laboratory-grown strains (Hijnen et al 2006). Previous studies have proven that some bacteria genus can easily cross the treatment process, while remaining are viable (Eddabra et al 2011;Fonteneau et al 2017); and this is further confirmed by the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Sadly, just few studies have been carried out in Agadir (Mimouni et al 2002(Mimouni et al , 2003Alla et al 2006;Eddabra et al 2011), which is particularly characterized by an arid climate, and high industrial and agricultural activities. Many of the reported studies in Agadir were focalized on chemical risks (Mouhanni et al 2011;Aba-aaki et al 2013) and microbiological hazards of reuse of wastewater (Touyer et al 1998;Mimouni et al 2002Mimouni et al , 2003Eddaoudi et al 2004;Eddabra 2011;Fonteneau et al 2017). The purpose of this study is to evaluate the possibility of reusing treated wastewater from the Mzar treatment plant in the irrigation of green spaces.…”
Section: Introductionmentioning
confidence: 99%
“…This rapid pace of innovation in public health laboratories across countries supports the ECDC vision of pan-European surveillance systems sharing WGS-based typing data for key diseases by 2020 ( 6 ). The present study indicated disparity of practice among reference laboratories in Europe (Figure 2 ), with some performing NGS on a limited basis, e.g., for outbreak investigations, while others are applying WGS-based typing on a much larger scale, e.g., for near real-time surveillance and outbreak detection, as previously reported at national level ( 3 , 6 , 13 , 16 20 ). This diversity of practice among countries may be partly linked to restriction to service capacity related to test costs ( 7 , 21 ) or, as identified in the herein study, lack of trained staff with sufficient bioinformatics expertise.…”
Section: Discussionsupporting
confidence: 64%
“…DNA macrorestriction, i.e., Pulsenet standard Xba I-PFGE protocol ( Ribot et al, 2006 ), and/or whole genome sequencing (WGS) were performed for Salmonella Mbandaka isolates. Sequencing and phylogenetic analyzes were done as previously described by Fonteneau et al (2017) . Furthermore, various genetic analyses, like Multi-Locus Sequence Typing (MLST) and acquired antibiotic resistance gene content determination, were determined on assembled sequences with web-based tools 2 and by an in-house Perl script.…”
Section: Methodsmentioning
confidence: 99%